Cardiac abnormalities in children with systemic lupus erythematosus - Günal, Nazlıhan; Kara, Nazlı; Akkök, Nermin; Çakar, Nilgün; Kahramanyol, Öz; Akalın, Nursel (The Turkish Journal of Pediatrics, 2003)
Children and adolescents with systemic lupus erythematosus (SLE, n = 14) with no cardiac symptoms were examined for cardiac involvement by physical examination, electrocardiography (ECG) and echocardiography. The indexes of left ventricular (LV) systolic and diastolic function were compared with the findings of 20 healthy, age-matched control subjects. Echocardiographic examination revealed mild tricuspid valve regurgitation in three, and moderate tricuspid and mitral valve regurgitation in two patients. Pericardial thickening was found in one patient. Indexes of LV systolic and diastolic function of SLE patients differed significantly from control subjects, with marked reduced ejection fraction (EF) and fractional shortening (FS) as well as reduced peak early diastolic filling velocity (E) and ratio of early-to-late diastolic filling velocity (E/A). Deceleration time (DT) was longer in the patients than in the control group. Late filling velocity (A) and isovolumic relaxation time (IRT) did not differ between the two groups. Valvular and pericardial involvement was found to be lower than previous reports. We conclude that asymptomatic diastolic and systolic dysfunction is common in children with SLE, most likely representing myocardial involvement. Routine cardiac evaluation by echocardiography can be recommended in the follow-up of children with SLE in order to detect silent cardiac abnormalities.